2021
DOI: 10.1111/1759-7714.13792
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Prognostic Score predicts chemotherapy‐triggered acute exacerbation‐interstitial lung disease in patients with non‐small cell lung cancer

Abstract: Background Interstitial lung disease (ILD) in patients with non‐small cell lung cancer (NSCLC) worsens the prognosis for overall survival (OS) due to chemotherapy‐triggered acute exacerbation (AE)‐ILD. The Glasgow Prognostic Score (GPS), which is based on serum C‐reactive protein and albumin levels, has been suggested as a reliable prognostic tool for mortality in cancer patients, including NSCLC. In this study, we investigated whether GPS is a predictor for chemotherapy‐triggered AE‐ILD and the prognosis in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
(87 reference statements)
0
18
0
Order By: Relevance
“…35 Patients with sarcopenia have been found to have reduced PGC-1α in their skeletal muscle but enhanced interleukin-6 and tumor necrosis factor-α expression, causing inflammation and muscle proteolysis 36,37 Previous studies have suggested that inflammation and undernutrition may contribute to the prognosis and exacerbation of ILD. 14,[38][39][40][41] Based the aforementioned findings, anti-inflammatory treatment through myokine supplementation and maintenance of muscle mass through nutrition therapy and rehabilitation may be novel approaches for suppressing ILD exacerbation, as well as improving the prognosis for lung cancer with ILD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Patients with sarcopenia have been found to have reduced PGC-1α in their skeletal muscle but enhanced interleukin-6 and tumor necrosis factor-α expression, causing inflammation and muscle proteolysis 36,37 Previous studies have suggested that inflammation and undernutrition may contribute to the prognosis and exacerbation of ILD. 14,[38][39][40][41] Based the aforementioned findings, anti-inflammatory treatment through myokine supplementation and maintenance of muscle mass through nutrition therapy and rehabilitation may be novel approaches for suppressing ILD exacerbation, as well as improving the prognosis for lung cancer with ILD.…”
Section: Discussionmentioning
confidence: 99%
“…(3) ILD that could not be completely explained by pulmonary infectious disease, heart failure, or fluid overload; and (4) a less than 4-week interval between the last chemotherapy administration and onset of ILD exacerbation. 9,10,13,14,30 The following patients were excluded: those (1) whose CT images did not include the spinous process at the third lumbar vertebral level, (2) who had other concomitant active malignancies, infectious diseases, or congested cardiac failure upon initial presentation, (3) who had insufficient clinical data, (4) who had been taking systemic steroids, (5) who had secondary ILD (i.e., interstitial pneumonia associated with connective tissue disease or antineutrophil cytoplasmic antibody-associated ILD), (6) who had received contraindicated chemotherapeutic drugs in Japan for patients with ILD (i.e., gemcitabine and epidermal growth factor receptor tyrosine kinase inhibitor), and (7) who received thoracic irradiation.…”
Section: Patientsmentioning
confidence: 99%
“…First, this was a single-center retrospective study with a relatively small sample size, which may introduce bias. However, lung cancer with ILD is a rare disease with a limited number of patients 3,4,9,10,[12][13][14]38,40 . The number of patients included herein does not considerably differ from those included in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…ILD was diagnosed when ground-glass attenuation and reticulation shadow or honeycombing with/without peripheral traction bronchiectasis were observed in both lung elds on chest HRCT. Diagnoses of chemotherapy-triggered ILD exacerbation were made in accordance with the following criteria detailed in previous studies: (1) deterioration of dyspnea; (2) new bilateral ground-glass attenuation and/or consolidation superimposed on pre-existing interstitial shadows; (3) ILD that could not be completely explained by pulmonary infectious disease, heart failure, or uid overload; and (4) a less than 4-week interval between the last chemotherapy administration and onset of ILD exacerbation 9,10,13,14,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation